Optimasi Dan Identifikasi Fitokimia Serta Uji Efek Hipoglikemik Kombinasi Ekstrak Daun Dandang Gendis (Clinacanthus nutans) Dan Ekstrak Ciplukan (Physalis angulata L.) Secara In Vitro - U. Widayat; Chaidir Chaidir; Siswa Setyahadi (Faculty of Pharmacy, Universitas Muslim Indonesia, 2022)
Diabetes mellitus is a metabolic disease characterized by hyperglicemic. Dandang Gendis (Clinacanthus nutans) and Ciplukan (Physalis angulata L.) are plants which recognized as blood glucose controller. The study aims to determine the effectiveness of the combination of the two extracts in decreasing blood sugar levels in vitro. The leaves of dandang gendis and ciplukan were extracted with various solvents (hot water, cold water, 96% ethanol, 75% ethanol, 50% ethanol and 30% ethanol were used as solvents), then tested the quality of the simplicia and extract, then the phytochemical test of each extract, after that the hypoglycemic activity of each extract was tested, made several variations of the dose, then tested the antidiabetic activity of the combination extract, calculated percent protection and percent effectiveness of single extract and a combination of leaf extract of dandang gendis (Clinacanthus nutans) and ciplukan (Physalis angulata L).The results showed that inhibition of the α-amylase enzyme by extracts of Dandang Gendis, Ciplukan and their combinations included the combination of EE96% 10 mg (1:1) of 1.25 ppm; Combination of EE96% 10mg (1:2) of 6.340 ppm; Combination of EE96% 10mg (2:1) of 5.808 ppm; The combination of EE96% 10mg (2:2) was 7.115 ppm and the IC50 acarbose value was 4.23 ppm. Dandang Gendis extract, Ciplukan and their combination had α-amylase inhibitory activity which was not significantly different between the extract and the control Acarbose. Inhibition of α-amylase enzyme activity could be influenced by metabolites and total phenolic extracts of Gendis, Ciplukan and their combinations.